The last kids on Earth and the cosmic beyond - Brallier, Max (Brallier, Max. Last kids on Earth, 2018)
Jack and his fellow kid survivors are determined to make the most of the winter and all the snowballs and celebrating that comes with the season, despite the reality that the Monster Apocalypse is in full swing around them. But when a fellow human survivor steals Jack's best monster-slaying device, the team must face down a villain even darker than the monsters they've been fighting.